Differentiation of external morphology of Oribatulidae (Acari: Oribatida) in light of the ontogeny of three species - Seniczak, Stanisław; Seniczak, Anna (Zootaxa, 2012)
In this paper the differentiation of external morphology and ontogeny of Oribatulidae were investigated, on the basis ofPhauloppia lucorum (C. L. Koch, 1841), Lucoppia burrowsi (Michael, 1890), and Oribatula tibialis (Nicolet, 1855),which ontogeny is described and illustrated here for the first time. The juveniles of these species have smooth cuticle, aclavate sensillus with barbed head, and similar formulae of coxisternal, genital and aggenital setae, but differ mainly inbody size, formulae of gastronotal setae, number of setal excentrosclerites on the gastronotum, and shape of some setae.The number of setal excentrosclerites and presence of seta h 3 in larva differ the juveniles of Ph. lucorum and L. burrowsifrom those of O. tibialis, and seem to have generic value, and are also associated with the number of notogastral setae inadults (14 pairs in two former species, 13 pairs in latter species). The juveniles of O. tibialis lack excentrosclerite at setalm, comparing to those of Ph. lucorum and L. burrowsi, and this morphological character is shared with ScheloribatesBerlese, 1908 and Liebstadia Oudemans, 1906 from the family Scheloribatidae. The larva of O. tibialis lacks seta h 3 , sim-ilarly as that of Scheloribates, while the larvae of Ph. lucorum, L. burrowsi, and Liebstadia have this seta. Presence ofsetal pair c 3 in adult of Zygoribatula cf. frisiae (Oudemans, 1900) is recorded here for the first time, which indicates the order of loss of setae of c-series in Oribatulidae according to Grandjean (1951, 1958, 1968).